Innovative technique for the study of pneumoperitoneum in the evaluation of abdominal pain after chemical irritation with zymozan - Crema,Eduardo (2008)
PURPOSE: To assess the influence of pneumoperitoneum in mice submitted to peritoneal irritation provoked by the biological agent Saccharomyces cerevisae, by counting the number of abdominal contractions elicited. METHODS: To study the effects of pneumoperitoneum analgesic action, 60 mice were divided into two groups: the experimental group, subjected to pneumoperitoneum; and the control group, without pneumoperitoneum. The both groups received intraperitoneal injection of zymosan at a dose of 1mg/0,2ml/mouse. RESULTS: The sum of the number of abdominal contractions of the experimental group (with pneumoperitoneum) was significantly lower than that of the control group (without pneumoperitoneum). In the experimental group, a lower number of contractions occurred in each min compared to the control. CONCLUSION: The observation of the analgesic effect of pneumoperitoneum using CO2 in mice submitted to peritoneal irritation by zymosan was verified.